A Critical Discourse Analysis of George Bush’s speech on September 11 attacks - Vi, Thị Bảo Thoa (2017)
This study attempts to discover the relationship between power, ideology and discourse embraced in the speech delivered by President G.W. Bush on the September 11, 2001, using the CDA framework suggested by Norman Fairclough. The analysis is carried out in three separated phases namely description, interpretation, and explanation. Major aspects selected for analysis include vocabulary, grammar, and macro-structure. An analytical framework is also built up in order to specify goals and analytical units in each stage. Following this framework, in-group and out-group lexicalization, voice, pronouns, large-scale structure and emotion techniques are investigated. The findings show thatideology and power are expressed throughout the address in a number of ways. Arousing the nation pride and heroism with tactful choices of vocabulary to construct two contrastive sides, exerting power and affirming utmost leader position with flexible uses of pronouns and voices, asserting ideology with shifts of focuses well-combined with emotion techniques, Bush actually makes the speech his powerful weapon in political battles.